PENGARUH PENYARADAN KAYU DENGAN TRAKTOR RANTAI KELABANG TERHADAP KERUSAKAN TEGAKAN TINGGAL - Maman Mansyur Idris; Yahya Fakuara; Gunarwan Suratmo; Rahardjo S Suparto (Jurnal Penelitian Hasil Hutan, 1988)
The  study   of  the  effect  of  log skidding  on  the  damage  of  residual stand  was carried out in one  logging company in West Kalimantan   in  1986.   The  meaning  of  residual stand  in the  study  are trees with diameter  20 cm and up.  The result of the study   shows  that  the  average damage  of  residual stand  is 18% per  hectare,  not  included  the damage  caused  by felling i.e.  15%  per  hectare.  According   lo  Indonesian   Selective  Cutting  System,  the  residual stand  is good  enough  to  fulfill  the sustained  yield  condition, that  is keep  at  least 25  core  trees  to  be left  per hectare. The role of skidded   trees number and stand  density  was significant  effect   on  the  residual stand  damage.